Ensuring Gender Equality in Customs Authorities Is an Important Factor (Zien Journal of Social Sciences and Humanities, 2024)
In this article, there are opinions about a number of reforms being carried out to ensure gender equality in customs authorities and their results, including the reforms being carried out in terms of attention and respect for women, the creation of the conditions are covered. Also, issues such as setting up institutional mechanisms for achieving the goal of "Gender Equality" in the customs authorities were revealed.